Iowa RBA, August 23, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Two emails for Iowa RBA updates for August 23, 1999. Highlights of the updates include sightings of a juvenile and adult Arctic Tern, MacGillivray's Warbler, Sabine's Gull, Red-necked Phalarope, Eurasian Collared Dove, Little Blue Heron, and Yellow-bellied Flycatchers. Epson - sheet feed/flatbed